Review of Space, Gender, and the Gaze in Literature and Art - Vékási, Adél (AMERICANA E-journal of American Studies in Hungary, 2018)
Space, Gender, and the Gaze in Literature and Art Edited by Ágnes Zsófia Kovács and László B. Sári Newcastle upon Tyne, UK: Cambridge Scholars Publishing, 2017 250 pages ISBN: 978-1-4438-3155-0